Construindo o movimento da responsabilidade social empresarial no Brasil: um estudo de caso sobre o Instituto Ethos - Duarte, Francisco José Mendes (2012)
This study aims to investigate the historical origins and ideological aspects underlying the discourse of the Instituto Ethos de Empresas e Responsabilidade Social. Thus, we seek to demonstrate, at the national level, that the democratic political thought advocated for such an historical roots in PNBE, the trade group that stood out on the national scene in the early 1990s and in which the current leaders of the Ethos were engaged. In turn, at the international level, Ethos has been influenced by the movement of sustainability, embracing the rhetoric of sustainable development, and also by the Amartya Sen s thought. Summing up, we will seek to understand how such influences rhetorical apply to the political project developed by Ethos, especially regarding the public policies.